Postcolonial Study on Guest by Camus in the lens of Homi Ke Bhabha - Raouf Aminzadeh; Fatemeh Sadat Basirizadeh; Narges Raoufzadeh; Shiva Zaheri Birgani (Britain International for Academic Research (BIAR-Publisher), 2022)
The aim of this study is to discuss use of Postcolonial Study on Guest by Camus in the lens of Homi Ke Bhabha. The result of this study shows that The Arab was